Archaeo-inspired material synthesis: sustainable tackifiers and adhesives from birch bark. Issue 4 (14th September 2018) - Lang, Johann; Dörrstein, Jörg; Zollfrank, Cordt
Abstract : Pitch obtained through pyrolysis of the outer bark of birch trees ( Betula pendula ) belongs to the oldest thermoplastic glues fabricated by mankind. Inspired by archaeological findings, several products with beneficial properties for modern adhesive applications were generated through torrefaction of white birch bark from 260 to 340°C. The process was inspired by the ancient two-pot method. Solvent extraction with acetone was applied to isolate the specific adhesive compounds from the torrefaction residue. The chemical structure of the products was completely identified for the first time. The obtained betulin esters of suberin and suberinic fatty acids represent a new class of tackifying agents suitable for adhesive applications. The products exhibit excellent adhesive properties, and the glass transition temperature T g could be adjusted between −11 and 52°C by controlling the pyrolysis temperature and duration. Products with a T g higher than 30°C are well suited as tackifying agents for adhesives, while pitches with a lower T g can be used as low-viscosity hot melts. The fabricated archaeo-inspired adhesives can be obtained in very high yields (15–27% (m/m)) and are virtually odourless.